Strengthening Students’ Understanding of Religious Symbols and Tolerance through the Jelajah Simbol Harmoni Educational Board Game - Hidayat, Samsul; Irfani, Amalia (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to implement the Jelajah Simbol Harmoni educational board game as an innovative learning medium to enhance students’ understanding of religious symbols and foster tolerance in secondary schools. Grounded in the perspectives of Religious Studies and interfaith relations, the program responds to the limited availability of contextual learning media for promoting religious moderation. The program was implemented in three secondary schools in Pontianak City, involving 20 students and three religious education teachers. A participatory-educative approach was employed through three stages: preparation, implementation, and evaluation. Data were collected using pre-test and post-test instruments, observation sheets, and semi-structured interviews, and were analyzed descriptively using a mixed-methods design. The findings indicate a significant improvement in students’ understanding of religious symbols, as reflected in the increase in average scores from 55 to 80. Observational data also revealed high levels of student engagement, with 85% of participants successfully completing game challenges and demonstrating cooperative and tolerant attitudes. These results confirm that Jelajah Simbol Harmoni is effective as an alternative pedagogical strategy for strengthening students’ understanding of religious symbols and promoting tolerance in secondary school contexts.